Development and evaluation of a Register-Based Organ Damage Index in systemic lupus erythematosus: a nationwide, population-based study from Sweden - Elizabeth V Arkema; Christopher Sjöwall; Ioannis Parodis; Alvaro Gomez; Muna Saleh; Julia F Simard (Lupus Science and Medicine, 2025)
Objective To develop a Register-Based Organ Damage Index (RBODI) in SLE, and evaluate its accuracy in estimating Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) Damage Index (SDI) scores. Additionally, to describe organ damage accrual and associations with mortality in a Swedish population-based nationwide cohort.Methods SDI items were translated into diagnosis, treatment and procedural codes retrieved from Swedish health registers. RBODI was calculated using the same rules as the SDI and its accuracy was evaluated using SDI data from the Clinical Lupus Register in North-Eastern Gothia cohort as the gold standard. Among newly diagnosed patients with SLE from Sweden (2005–2021), we estimated 5-year risks of organ damage, and adjusted HRs of first RBODI-based organ damage accrual associated with patient characteristics. Lastly, we estimated the association between RBODI-based organ damage within 5 years of diagnosis and mortality.Results The evaluation cohort included 271 prevalent cases (65.3% developed organ damage). RBODI had a positive predictive value of 90%, sensitivity 80% and specificity 83%. Among 4441 newly diagnosed patients with SLE, 40% developed organ damage within 5 years. Males had a 30% higher risk of developing damage compared with females (HR 1.3) and older individuals (>45 years old compared with younger) had more than threefold higher risk (HR 3.3). Early development of organ damage was associated with a 2.1-fold higher risk of mortality.Conclusion Our novel RBODI accurately estimates SDI scores and describes long-term trends in damage accrual in the largest cohort of incident SLE to date. The strong association between early damage accrual and mortality highlights the need for efficient prevention strategies.